Negative Correlation Between Emotional Intelligence and Adolescent Aggression: Korelasi Negatif Antara Kecerdasan Emosional dan Agresi Remaja - Chusnul Widya; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Adolescence is marked by psychological and emotional transitions that can trigger behavioral instability. Specific Background: Aggressive behavior among students, including physical, verbal, emotional, and cognitive hostility, is increasingly observed, while emotional intelligence is linked to self-awareness, emotional control, empathy, motivation, and social interaction skills. Knowledge Gap: Empirical data examining the statistical relationship between emotional intelligence and aggressive behavior among vocational high school students, particularly in SMK X Sidoarjo, remains limited. Aims: This study investigates the relationship between emotional intelligence and aggressive behavior among vocational adolescents. Results: A quantitative correlational approach involving 289 students revealed a significant negative relationship between emotional intelligence and aggressive behavior (p = 0.012; r = -0.133). Emotional intelligence contributed 1.8% to the variance in aggressive behavior, with most students showing moderate levels of both variables. Novelty: This study provides empirical statistical evidence regarding the association between emotional intelligence and aggressive tendencies in Indonesian vocational adolescents. Implications: The findings offer academic and practical insights for educators and school counseling services in developing emotional intelligence programs to address aggressive tendencies among students. Highlights: Statistical Testing Confirmed a Significant Inverse Association Between Measured Psychological Variables. Most Participants Demonstrated Moderate Levels Across Both Measured Constructs. The Measured Psychological Predictor Accounted for a Small Proportion of Behavioral Variance. Keywords: Emotional Intelligence, Aggressive Behavior, Adolescents, Vocational Students, Correlational Study